Feasibility study of using various optical filters in conjunction with indoor visible light communication system - Fadhil, Hilal A.; Alattar, Feras Hasson; Fadil, Tariq Adnan (Oficyna Wydawnicza Politechniki Wrocławskiej, 2023)
In modern telecommunication engineering, visible light communication (VLC) is developing a competitive advantage over the traditional RF data communication model since it uses light to transmit data. Optical filters play an important role in optical communication systems to enhance the transmission rate of bit-error rate (BER), especially as a result of noisy environments. We investigate the VLC signal performance induced by four types of filters, including Bessel, Gaussian, rectangular, and trapezoidal filters. The BER is considered an important aspect of improving optical system performance, as it indicates less crosstalk and fewer interferences within the system and is analyzed using eye diagram opening penalties. In our simulation results, the Gaussian filter performs best among these four types of filters. In this paper, a VLC indoor model is developed and simulated using an eye diagram, a bit error rate, and a transmission distance for the proposed model. The results from this study show significant improvements of Gaussian filter over other optical filters for next-generation optical networking systems, the overall BER of a Gaussian filter-based indoor VLC system is less than 9.6 × 10–15, when the bandwidth of the optical filter is 5 nm at the quality factor of 14 dB.
Optica Applicata, Vol. 53, 2023, nr 4, s. 511-522
Optica Applicata is an international journal, published in a non-periodical form in the years 1971-1973 and quarterly since 1973. From the beginning of the year 2008, Optica Applicata is an Open Access journal available online via the Internet, with free access to the full text of articles serving the best interests of the scientific community. The journal is abstracted and indexed in: Chemical Abstracts, Compendex, Current Contents, Inspec, Referativnyj Zhurnal, SCI Expanded, Scopus, Ulrich’s Periodicals Directory
http://opticaapplicata.pwr.edu.pl/
Keywords: optyka; VLC; LED; optical filter; BER